Molecular Mono-Dikaryon discrimination of fungi “Pleurotus sajor-caju” - Avin, F.A.; Bhassu, S.; Vikineswary, S. (2010)

(untitled)
All 62 single spore isolates of Pleurotus sajor-caju (monokaryons) could be clearly discriminated from their parents (dikaryons) by amplification of the partial sequence of nuclear ribosomal DNA. Moreover, by using the sequence data, two different types of monospore were identified that will provide very useful background for further breeding and fusion purpose.